Improving Students' Science Process Skills through PjBL learning assisted by collaborative project LKPD - Novianto, Eko (Reflection Journal, 2023)
This research aims to enhance students' science process skills in static electricity through the implementation of Project-Based Learning (PjBL) model aided by Collaborative Project Worksheets. The research method employed is Classroom Action Research. The research subject comprises 24 ninth-grade students from SMP Negeri 1 Jereweh. The results indicate a significant improvement in students' science process skills from the first cycle to the second cycle, with an average increase of 30.6%. The implementation of the PjBL model with LKPD has also proven effective in enhancing student engagement in learning and facilitating the development of social skills. Recommendations for further research include expanding the scope of study, deepening understanding of factors influencing the implementation of the model, and exploring its effects on other aspects of learning such as student motivation and mastery of concepts. This research provides valuable insights into the potential and benefits of the PjBL approach with LKPD in enhancing the effectiveness of learning in schools. Thus, through this approach, it is hoped to create a more dynamic learning environment focused on comprehensive student skill development..